2021
DOI: 10.1088/1741-2552/abe356
|View full text |Cite
|
Sign up to set email alerts
|

Visual cues added to a virtual environment paradigm do not improve motor arrests in Parkinson’s disease

Abstract: Objective. Elucidating how cueing alleviates freezing of gait (FOG) in Parkinson's disease (PD) would enable the development of more effective, personalized cueing strategies. Here, we aimed to validate a visual cueing virtual environment (VE) paradigm for future use in e.g. neuroimaging studies and behavioral studies on motor timing and scaling in PD patients with FOG. Approach. We included 20 PD patients with FOG and 16 age-matched healthy control subjects. Supine participants were confronted with a VE displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…Second, our study clearly showed that gait parameters like gait speed and step length could be modulated with AR cues relative to one’s baseline gait pattern. This is encouraging considering earlier research with AR cues showing limited effects on various gait parameters ( 19 , 23 25 , 28 , 48 ). AR cues, when delivered through state-of-the-art AR headsets which have a sufficiently large vertical AR-FOV size, may thus be used to improve Parkinsonian gait.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Second, our study clearly showed that gait parameters like gait speed and step length could be modulated with AR cues relative to one’s baseline gait pattern. This is encouraging considering earlier research with AR cues showing limited effects on various gait parameters ( 19 , 23 25 , 28 , 48 ). AR cues, when delivered through state-of-the-art AR headsets which have a sufficiently large vertical AR-FOV size, may thus be used to improve Parkinsonian gait.…”
Section: Discussionsupporting
confidence: 66%
“…It is, however, unknown whether participants processed spatial information of the footprints in the air, on the ground, or both. The action-relevance, an important factor for effective cueing ( 47 ), of such step-length cues in the air is probably much lower [i.e., as the spatial information conveyed by the cues is not directly specifying the actual foot-placement locations ( 48 )] than when participants can directly step onto stepping targets on the ground, for which existing visuolocomotor control mechanisms can be utilized ( 49 52 ). The second additional benefit that we explored was adding mud sounds to dinosaur footprints to augment steps.…”
Section: Discussionmentioning
confidence: 99%